Maturation of the Central Auditory Nervous System in Children with Auditory Processing Disorder - Tomlin, Dani; Rance, Gary (Seminars in Hearing, 2016)
Neurodevelopmental delay has been proposed as the underlying cause of the majority of cases of auditory processing disorder (APD). The current study employs the cortical auditory evoked potential (CAEP) to assess if maturational differences of the central auditory nervous system (CANS) can be identified between children who do and do not meet the diagnostic criterion for APD. The P1-N1 complex of the CAEP has previously been used for tracking development of the CANS in children with hearing impairment. Twenty-seven children (7 to 12 years old) who failed an APD behavioral test battery were age-matched (within 3 months) to children who had passed the same battery. CAEP responses to 500-Hz tone burst stimuli were recorded and analyzed for latency and amplitude measures. The P1-N1 complex of the CAEP, which has previously been used for tracking development of the CANS in children with hearing impairment, showed significant group differences. The children diagnosed with APD showed significantly increased latency (∼10 milliseconds) and significantly reduced amplitude (∼10 μV) of the early components of the CAEP compared with children with normal auditory processing. No significant differences were seen in the later P2 wave. The normal developmental course is for a decrease in latency and increase in amplitude as a function of age. The results of this study are, therefore, consistent with an immaturity of the CANS as an underlying cause of APD in children.
Keywords: Cortical auditory evoked potential; central auditory nervous system development; auditory processing disorder